Tiempo malgastado. Sobre el aplazamiento de la escritura en tres novelas hispanoamericanas - Rodríguez, Amán Rosales (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In the last decades, many studies have proliferated on the different ways in whicha specific modality of consumer society, characterized by an unbridled acceleration of therhythms of production and work, affects the lives of millions of people, especially in highlyindustrialized nations. These studies suggest that the individuals, under the pressure of anincreasingly accelerated and frenetic pace of life, are compelled to perform certain roles andachieve certain goals that, if satisfactorily fulfilled, could guarantee success, or, at least, socialacceptance. But what happens when you cannot or do not want to perform and fulfil suchroles and expectations fast enough, when the individual prolongs or just abandons the entrustedtask? In the richly diverse world of Latin American fiction, many writers have tackled thisquestion. In base of three novels of different years: El libro vacío (1958), by the Mexican JosefinaVicens, Wasabi (1994), by the Argentine Alan Pauls, and La novela luminosa (2005), by the UruguayanMario Levrero, this paper comments the role played in contemporary fiction by thefigure of the apathic, indolent or just slow-moving writer. The main characters of those novelsseem to live in a slow-time dimension opposed to the fast one dominant in late modernity